Organizations For Growth: the Human Resource Contribution.: The Role of Technology in Transforming Human Resource Management (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The traditional style mainly focuses on supportive personnel activitiesfor a company, for example, collecting employee information, monitoringindividual performance, and implementing organization policies. It is apassive, submissive execution, without self-motivated participation intostrategic issue to foresee the challenges of tomorrow. Therefore, there comes ademand for the new HRM that should understand the business strategy, formulatethe corresponding management strategy on human resources to improve deliveredservice, and act as a strategy partner with top management team. To meet thedemand, there is an increasing pressure on HRM to support strategic objectivesand to focus on value-adding activities, which consequently leads to the changein the job content and the expectations on Human Resource (HR) professionals.Note that one of such changes is that the wide, contemporary use of InformationTechnology (IT) in supporting various HR activities. Moreover, the researchersexpect that the increasing use of Human Resource Information Technology (HRIT)can improve the performance of HR professionals and makes them involved in thecompany internal consulting activities.